HUBUNGAN PENGETAHUAN DAN SIKAP PSK DENGAN KEMAMPUAN MEYAKINKAN PELANGGAN UNTUK MENGGUNAJAN KONDOM DI LOKALISASI PSK DOLOKSANGGUL KECAMATAN DOLOKSANGGUL KABUPATEN HUMBANG HASUNDUTAN TAHUN 2013 - Margaret LV Simamora; Heru Santosa; Maya Fitria (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACT Sexually transmitted diseases (STDs) including HIV and AIDS infection is mostly transmitted through sexual intercourse both with couples who have already contracted the disease as well as who often alternated between a couple. Commercial sex workers is one trigger the transmission of sexually transmitted diseases, especially HIV and AIDS. This research aims to know the relationship between knowledge and attitude of commercial sex workers with ability to convince customers to use condom in district Doloksanggul 2013. This type of research is a survey of analytical by using the cross-sectional design, the population in the study were all is in 3 localization of commercial sex workers in Doloksanggul Subdistrict, namely amounting to 63 people and used as the total sampling. The data obtained by interview using a questionnaire and analyzed by chi-square test.. From the results of chi-square test (α<0.05), indicating there is a significant relationship between the knowledge with the ability to convince customers to use condoms (p = 0.002). And shows there is a significant relationship between attitude with ability to convince customers to use condoms (p = 0.032). The commercial sex workers is expected to be more able to provide protection to himself by improving the ability to convince customers to use condom. And to the local goverment to better reproduce the division of condom to the commercial sex workers. Keywords : Knowledge, Attitude, Condoms, Commercial Sex Workers